Srovnání výsledků revizní rekonstrukce předního zkříženého vazu kolenního kloubu kadaverózním BTB štěpem s výsledky po primární rekonstrukci LCA s odfiltrováním efektu věku a pohlaví - Heger, Jan; Rouchal, Marek; Vališ, Petr; Sklenský, Jan; Novák, Jan; Maršálek, Miloslav (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2021)
PURPOSE OF THE STUDY Evaluation of the success rate of revision ACL reconstruction using the cadaverous BTB allogeneic graft and comparison of the outcomes achieved with the data of patients after the primary ACL reconstruction using the autologous BTB graft with filtering out the potential effect of diversity of the groups of patients as concerns sex and age. MATERIAL AND METHODS The evaluated outcomes of 34 patients operated in the period 2004-2017, i.e. with the minimum follow-up period of three years, were compared with the outcomes of 34 patients selected individually so that in pairs the age and sex are identical - 10 women and 24 men in the range of age from 20 to 44 years, with the median of 29 years at the time of surgery. The assessment and comparison of the outcomes achieved are done according to the Lysholm and Tegner scores. RESULTS The mean Lysholm score of the patients after the revision ACL reconstruction using the cadaverous BTB allograft achieved 54.7 points preoperatively, 72.3 points at the 1-year follow-up and 77.4 points at the 3-year follow-up. The Tegner score at the time of full performance before the injury was 7.7 points, whereas it was 5.8 points after the injury and 6.5 points three years after the surgery. In the group of patients after the primary ACL reconstruction using the autologous BTB graft, the Lysholm score was 64.4 points preoperatively, 85.1 points one year postoperatively and 88.2 points three years postoperatively. The results according to the Tegner score achieved by the primary control group at respective follow-up periods were 6.7 points, 5.1 points and 6.2 points respectively. DISCUSSION The increase in the number of performed ACL reconstructions leads also to an increase in the number of revision surgeries. This trend is also fuelled by the change in the lifestyle, the shift in age-related indication criteria for surgery, and other factors. The realistic expectations regarding the outcome of the revision ACL reconstruction shall take into account the effect of multiple insults that the knee must withstand. Even though subjective improvement of the knee condition is usually experienced postoperatively, the achieved outcomes tend to be less positive than in primary reconstructions. The return to the original pre-injury level of sports activities is achieved less frequently after revision surgeries. CONCLUSIONS The revision surgery of ACL rupture using the cadaverous BTB graft is a safe and reliable technique. It has a potential to improve the subjective satisfaction of the patient, nonetheless the mean postoperative Lysholm score is not so high as that achieved in patients after primary ACL reconstruction. Key words: anterior cruciate ligament, revision ACL reconstruction, cadaverous BTB graft, ACL graft rerupture.
Keywords: Anterior Cruciate Ligament Injuries; ligamentum cruciatum anterius; Humans; poranění předního zkříženého vazu; Female; mladý dospělý; dospělí; výsledek terapie; lidé; reoperace; rekonstrukce předního zkříženého vazu; Anterior Cruciate Ligament Reconstruction; Adult; Knee Joint; ženské pohlaví; Male; Retrospective Studies; Treatment Outcome; Young Adult; retrospektivní studie; mužské pohlaví; Reoperation; Anterior Cruciate Ligament; kolenní kloub